The Effect Of The Viral Marketing Song On The Millenial Generation’s Buying Interest - Husnusyifa, Annisa; Mujianto, Haryadi (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
This research was motivated by a jazz singer named Tulus from Bandung, whose song went viral in March 2022. “Hati-Hati di Jalan” managed to occupy the 42 Global Top 50 on Spotify. This indicates that the song is worldwide and enjoyed by global listeners, including the millennial generation. According to Chart Data, the Indonesian song managed to become the first in history to occupy that position. The presence of viral marketing can also help Spotify to introduce its songs more effectively, massively and quickly to the millennial generation. The purpose of this study was to find out how high the influence of viral marketing for the song